2021
DOI: 10.14238/pi61.1.2021.39-45
|View full text |Cite
|
Sign up to set email alerts
|

New PELOD-2 cut-off score for predicting death in children with sepsis

Abstract: Background According to the most recent Sepsis-3 Consensus, the definition of sepsis is life-threatening organ dysfunction caused by dysregulated immune system against infection. Currently, one of the most commonly used prognostic scoring system is pediatric logistic organ damage-2 (PELOD-2) score. Objective To determine and validate the pediatric logistic organ dysfunction-2 (PELOD-2) cut-off score to predict mortality in pediatric sepsis patients. Methods A prospective cohort study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…16 With an individual cut-off, the diagnostic performance was similar among all three scores. This was also reported by Melda et al (2021) 14 and Suari et al (2021) 17 , who did not find any significant differences in the accuracy, sensitivity, specificity, positive predictive value, or negative predictive value in the PELOD-2 score with and without the lactate variable. This could be explained by the multivariable logistic regression analysis findings, which revealed that the blood lactate variable was not statistically significant (p-value=0.557).…”
Section: Diagnostic Performancesupporting
confidence: 84%
“…16 With an individual cut-off, the diagnostic performance was similar among all three scores. This was also reported by Melda et al (2021) 14 and Suari et al (2021) 17 , who did not find any significant differences in the accuracy, sensitivity, specificity, positive predictive value, or negative predictive value in the PELOD-2 score with and without the lactate variable. This could be explained by the multivariable logistic regression analysis findings, which revealed that the blood lactate variable was not statistically significant (p-value=0.557).…”
Section: Diagnostic Performancesupporting
confidence: 84%
“…The incidence of sepsis is influenced by age, underlying conditions, and infection source. 20,21 Children under five have immature immune systems, thus they are more likely to get serious infections or even sepsis. 22 In our study, respiratory illness was the primary disease leading to organ dysfunction in septic children.…”
Section: Discussionmentioning
confidence: 99%